Women’s Health Under Sustainable Development Goal 5: A Neglected Discourse - Ahmed, Sufiya; Upadhyay, Sudhanshu (Frontiers in Law, 2024)
Sustainable Development Goal 5 (SDG 5) contemplates minimizing the gap between men and women and achieving gender equality and empowering all women and girls by the year 2030. It categorizes the goal of gender equality and empowerment of all women into nine more sub-divisions. Target 6 talk about to “Ensuring universal access to sexual and reproductive health and reproductive rights as agreed in accordance with the Programme of Action of the International Conference on Population and Development and the Beijing Platform for Action and the outcome documents of their review conferences.” As per the World Health Organization, right to health must be ensured to every person, it states that "the enjoyment of the highest attainable standard of health is one of the fundamental rights of every human being without distinction of race, religion, political beliefs, economic or social conditions.” However, research has shown that how this basic human right is being denied to women in the name of socio-religious & cultural beliefs which are responsible for deterioration of women’s health altogether. Socially, women are considered powerless and weaker sex. Culturally, they have to be at all times in the service of every member of the household and as such, are the last person to be bothered about. And biologically, as the structure of women’s body does not remain as static as of men rather it undergoes to drastic change with the growth of their age where a woman has to face myriads of health related issues owing to her sexual and reproductive organs, instead of addressing these health issues medically, people often choose to overlook it as their mind consider such issues as “women’s problem” about which one cannot do anything as if she is destined to develop these health problems just because she is a woman. This paper critically analyzes the health status of women in India and also suggests for a good healthcare system to achieve the goal of gender equality as given in Sustainable Development Goal 5.